2016
DOI: 10.1002/pits.21977
|View full text |Cite
|
Sign up to set email alerts
|

PUBLICATION OUTLETS FOR SCHOOL PSYCHOLOGY FACULTY: 2010 to 2015

Abstract: Many school psychology faculty are required to publish for purposes of retention and promotion. It is useful to have an understanding of the different outlets for scholarly publications. In the present study, we investigated the peer-reviewed journals in which school psychology faculty were published between 2010 and 2015, the number of articles in each journal, and the acceptance rates and impact estimates for each journal. We identified school psychology faculty using the National Association of School Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 11 publications
4
51
0
Order By: Relevance
“…All nine journals included in the analysis are peer‐reviewed and all, except the International Journal of School and Educational Psychology , were found to be the most common publication outlets for school psychology faculty in Hulac and colleagues’ () aforementioned review. In addition to this criteria, these journals were included in the analysis because they had the terms “school” and “psychology” in the title, focus on psychological/mental health, learning/educational processes and/or practices for children and adolescents, and have impact in the field, with several having an explicit focus on the field of school psychology (i.e., School Psychology Review , Journal of Applied School Psychology , Contemporary School Psychology , and School Psychology International ).…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…All nine journals included in the analysis are peer‐reviewed and all, except the International Journal of School and Educational Psychology , were found to be the most common publication outlets for school psychology faculty in Hulac and colleagues’ () aforementioned review. In addition to this criteria, these journals were included in the analysis because they had the terms “school” and “psychology” in the title, focus on psychological/mental health, learning/educational processes and/or practices for children and adolescents, and have impact in the field, with several having an explicit focus on the field of school psychology (i.e., School Psychology Review , Journal of Applied School Psychology , Contemporary School Psychology , and School Psychology International ).…”
Section: Methodssupporting
confidence: 80%
“…In a review conducted by Hulac et al. (), it was found that from 2010 to 2015, over three‐quarters of school psychology faculty in NASP‐approved programs published work in journals that did not have a specific school psychology focus (e.g., Journal of Psychoeducational Assessment , Assessment for Effective Intervention , and School Mental Health ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, publication outlets of faculty employed in the United States were recently and comprehensively reported by Hulac et al. (), and we did not aim to replicate that study or similar studies (Carper & Williams, ; Kranzler et al., ).…”
Section: Methodsmentioning
confidence: 95%
“…), Hulac et al. () examined faculty in National Association of School Psychologists–approved Ph.D. and Ed.S. school psychology programs in the United States.…”
Section: Publication Outlets Of Scholars In School and Educational Psmentioning
confidence: 99%